Mucus Drying Shortly After Birth Using Clay Adsorbent Effectively Maintained Temperature, Performance, Behaviour, and Reduced Mortality In Pre-Weaning Piglets - Besse Tenri Nurul Hikmah; Tri Satya Mastuti Widi; Ika Sumantri; Sigit Bintara; Tristianto Nugroho; Hamdani Maulana; Erika Kusuma Wardani (Jurnal Veteriner, 2025)
This study was aimed to determine the effect of mucus drying methods on newborn piglets on their postnatal behavior and preweaning performance. The research was conducted from February to May 2024 at a smallholder pig farm in Godean District, Sleman Regency, Yogyakarta. Treatments were applied to 66 newborn Landrace crossbred piglets and consisted of no drying assistance (P1), drying assistance using cloth (P2), and drying assistance using a clay as adsorbent (P3). The variables observed included body temperature, drying time, suckling time, postnatal behavior, and pre-weaningperformance. Behavior was recorded and analyzed using Closed-Circuit Television (CCTV) video footage. The data were analyzed using Analysis of variance and Analysis of covariance with the R programming language. The P3 treatment significantly (p<0.05) influenced body temperature at the 120th minutes and 24 hours after birth, body weight at two weeks, average daily gain (ADG) at 0–2 weeks (138.75 g/day), body length at 2 and 4 weeks, and chest circumference at 2 and 6 weeks. The P3 group also exhibited the lowest mortality rate (13.33 vs. 21.74%). Furthermore, P3 affected behavior 24 hours after birth, particularly walking, standing, searching for the mother’s nipple, and lying down with other piglets. Overall, the use of clay adsorbent effectively maintained piglet body temperature during the first 120 minutes after birth and primarily influenced piglet performance during the early postnatal period, with no significant effects observed in the later stages. Additionally, the use of clay adsorbent reduced mortality rates and enhanced piglet activity levels, demonstrating its effectiveness in supporting early postnatal adaptation.